Factor Analysis That Affect Firm Value (Study On Banking Sector Companies Listed On The Indonesia Stock Exchange (IDX) In 2018-2022) - Hermawan, Chulita Novianti; Rahwana, Kusuma Agdhi; Oktaviani, Nita Fauziah (Universitas Dehasen Bengkulu, 2024)
Company value is one measure of the success of company management during its operating process. The purpose of this study was to determine how the effect of investment decisions as measured by Price Earning Ratio (PER), funding decisions as measured by Debt to Equity Ratio (DER), and dividend policy as measured by Dividend Payout Ratio (DPR) on firm value as measured by Price to Book Value Ratio (PBV) simultaneously or partially. The data used in this study are the annual financial statements of Banking sector companies listed on the Indonesia Stock Exchange (IDX) in 2018-2022 using purposive sampling techniques in the sample selection method. Based on the specified categories, the samples used in the study amounted to 10 companies. This research uses a quantitative descriptive approach. The data analysis tool used to test the research hypothesis is panel data regression analysis using E-Views version 12. The results of this study can be concluded that investment decisions, funding decisions, and dividend policy simultaneously have a significant effect on firm value. While partially investment decisions have a significant positive effect on firm value, funding decisions are negative and have no significant effect on firm value, and dividend policy has a significant negative effect on firm value.